Exclusionary violence : antisemitic riots in modern German history - Hoffmann, Christhard 1952- Hrsg; Bergmann, Werner 1950- HerausgeberIn; Smith, Helmut Walser 1962- HerausgeberIn (Social history, popular culture, and politics in Germany, 2002)
The "Hep Hep" Riots of 1819 : anti-Jewish ideology, agitation, and violence Stefan Rohrbacher -- Anti-Jewish Emotion and Violence in the 1848 : crisis of German society / Manfred Gailus -- Political culture and violence against minorities : the antisemitic riots in Pomerania and West Prussia / Christhard Hoffmann -- Konitz, 1900 : ritual murder and antisemitic violence / Helmut Walser Smith -- Out with the Ostjuden : the Scheunenviertel riots in Berlin, November 1923 / David Clay Large -- The November Pogrom of 1938 : participation, applause, disapproval / Wolfgang Benz -- Exclusionary Riots : some theoretical considerations / Werner Bergmann -- Continuities and discontinuities of anti-Jewish violence in modern Germany, 1819---1938 / Richard S. Levy